2016
DOI: 10.1180/claymin.2016.051.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical changes and associated decrease in tritiated water diffusivity after alteration of cement–bentonite interfaces

Abstract: Alteration of cement–bentonite interfaces and accompanying changes in diffusivity of tritiated water (HTO) was investigated experimentally using intact, hardened cement-paste specimens. The alteration by carbonate solution was accompanied by mineralogical changes at the interface and a decrease in the HTO diffusivity to ∼70 ± 7%of the initial value after a 180-day period. Another alteration in contact with compacted bentonite was accompanied by mineralogical changes at the interface and a decrease in the HTO d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Early experimental studies on clay-cement contacts utilized batch experiments to investigate the evolution of clay powder or compacted clay samples in alkaline solutions (Gaucher and Blanc 2006). More recently, experimental investigations have focused on examining the interactions between hardened cement/mortar/concrete and compacted clay, including mass transport processes across the cement-clay interface (Dauzeres et al 2010;Fernández et al 2016;Yamaguchi et al 2016;Balmer et al 2017;Luraschi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental studies on clay-cement contacts utilized batch experiments to investigate the evolution of clay powder or compacted clay samples in alkaline solutions (Gaucher and Blanc 2006). More recently, experimental investigations have focused on examining the interactions between hardened cement/mortar/concrete and compacted clay, including mass transport processes across the cement-clay interface (Dauzeres et al 2010;Fernández et al 2016;Yamaguchi et al 2016;Balmer et al 2017;Luraschi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Melkior et al (2004) studied the evolution of the HTO and chloride diffusion coefficient of bentonite after contact with alkaline porewater; and observed a decrease of the diffusivity with increasing interaction time. Yamaguchi et al (2016) reported also a decrease of HTO diffusion coefficients to 70% of the initial value after 600 d in samples prepared from hardened cement paste and bentonite.…”
Section: Introductionmentioning
confidence: 86%
“…Experimental investigations on the cement-clay interfaces often use composite specimens consisting of cement/mortar/concrete and compacted clay (Sugiyama and Tsuji 2008;Dauzeres et al 2010;Shafizadeh et al 2015;Fernández et al 2016;Yamaguchi et al 2016;Balmer et al 2017) same as the first paper. More recently, long-term in-situ experiments in underground research laboratories (URL) on the cement-clay interfaces have also been conducted (Read et al 2001;Gaboreau et al 2012;Mäder et al 2017).…”
Section: Introductionmentioning
confidence: 99%